Heterobimetallic μ2-carbido complexes of platinum and tungsten. Issue 24 (5th June 2020) - Burt, Liam K.; Hill, Anthony F.
Abstract : The tungsten–platinum μ-carbido complex [WPt(μ-C)Br(CO)2 (PPh3 )2 (Tp*)] (Tp* = hydrotris(dimethylpyrazol-1-yl)borate) undergoes facile substitution of both bromide and phosphine ligands to afford a diverse library of μ-carbido complexes. Abstract : The tungsten–platinum μ-carbido complex [WPt(μ-C)Br(CO)2 (PPh3 )2 (Tp*)] (Tp* = hydrotris(dimethylpyrazol-1-yl)borate) undergoes facile substitution of both bromide and phosphine ligands to afford a diverse library of μ-carbido complexes that includes [WPt(μ-C)Br(CO)2 (dppe)(Tp*)], [WPt(μ-C)(NCMe)(CO)2 (PPh3 )2 (Tp*)]OTf, [WPt(μ-C)(S2 CNEt2 )(CO)2 (PPh3 )(Tp*)], [WPt(μ-C)(bipy)(CO)2 (PPh3 )(Tp*)]PF6, [WPt(μ-C)(phen)(CO)2 (PPh3 )(Tp*)]PF6, [WPt(μ-C)(terpy)(CO)2 (Tp*)]PF6, [WPt(μ-C)(CO)2 (PPh3 )(Bp*)(Tp*)], [WPt(μ-C)(CO)2 (PPh3 )(Tp*)2 ] and [WPt(μ-C)(bipy)(CO)2 (PPh3 )(Bm)(Tp*)], most of which have been structurally charcaterised.